2007
DOI: 10.1177/0960327107071867
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of radiation-induced clastogenicity by Aegle marmelos (L.) Correa in mice bone marrow exposed to different doses of γ-radiation

Abstract: The frequency of micronucleated polychromatic (MPCE), normochromatic erythrocytes (MNCE), and polychromatic/normochromatic erythrocyte ratio (PCE/NCE), was studied in the bone marrow of mice orally administered with 0, 200, 225, 250, 275 and 300 mg/kg body weight of hydroalcoholic leaf extract of Aegle marmelos (AME). Treatment of mice with AME, once daily for 5 consecutive days, before exposure to 2 Gy resulted in a significant decline in the frequency of MPCE when compared to the non-drug-treated ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
(70 reference statements)
2
19
0
Order By: Relevance
“…Additionally, preclinical studies have also confirmed that the Bael leaf extract has a high margin of drug safety and does not possess systemic, teratogenic, or genotoxic effects at optimal protective concentrations. 35,40,66,67 When these observations are considered along with its beneficial effects in the prevention and treatment of cancer, it is safe to assume that Bael remains a species with tremendous potential but only when the lacunae in the existing knowledge are bridged. The outcomes of such studies may be useful for the clinical applications of Bael in humans and may open up a new therapeutic avenue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, preclinical studies have also confirmed that the Bael leaf extract has a high margin of drug safety and does not possess systemic, teratogenic, or genotoxic effects at optimal protective concentrations. 35,40,66,67 When these observations are considered along with its beneficial effects in the prevention and treatment of cancer, it is safe to assume that Bael remains a species with tremendous potential but only when the lacunae in the existing knowledge are bridged. The outcomes of such studies may be useful for the clinical applications of Bael in humans and may open up a new therapeutic avenue.…”
Section: Resultsmentioning
confidence: 99%
“…38 The leaf extract prevented radiation clastogenesis in the cultured human peripheral blood lymphocytes and the bone marrow cells of mice, indicating its effectiveness as an antimutagen. 39,40 The phytochemical eugenol 41 is also reported to possess radioprotective effects and its presence in the extract may have contributed to these results.…”
Section: Protective Effects Of Bael and Its Phytochemicals Against Thmentioning
confidence: 99%
“…Recently, Abdullakasim et al have observed that A. marmelos fruit drink had high quantities of total phenolic compounds and was a good antioxidant [31] . A. marmelos leaf extract reduced radiation-induced DNA damage in cultured human peripheral blood lymphocytes and in mouse bone-marrow cells, indicating that A. marmelos is an efficient anticlastogen [32] . Transitional metals like iron, undergo redox cycling, resulting in production of ROS.…”
Section: Radioprotective Effectsmentioning
confidence: 94%
“…Petroleum ether extract contains fats and fixed oil while aqueous extract contains amino acids, tannins (condensed and pseudo tannins) and starch [5]. IR has been reported to possess various pharmacological actions, mainly antidiabetic [6], antiinflammatory [7], nephroprotective [8], antibacterial [9], antioxidant and antimicrobial activity [10]. Further, the principle constituents of IR such as sinapic and ferulic acids have exhibited behavioural and pharmacological…”
Section: Introductionmentioning
confidence: 99%
“…The bark as well as fruit is reputed to be a valuable Ayurvedic medicine for dysentery and various intestinal complaints [3,4]. It possesses potentmicrofilarial [5], radio protective [6], analgesic [7], antihyperglycemic, antidyslipidemic [8], anticancer [9,10] and antidiabetic activity [11,12]. Solvent extraction is most frequently used technique for isolation of plant metabolites.…”
Section: Introductionmentioning
confidence: 99%